Tanggung Jawab dan Kompetensi Notaris Pengganti dalam Pembuatan Akta (Jurnal Sosial Humaniora dan Pendidikan, 2025)
A notary is a public official who makes authentic deeds according to Article 1 paragraph (1) of Law of Law Number 2 of 2014 concerning the Amendment to Law Number 30 of 2004 on the Notary Position. In practice, there is a Substitute Notary who is temporarily appointed when the notary is absent. Although their authority is equal, the requirements for their appointment are lighter, creating normative disparities that impact the quality and legal certainty of the deed. This normative-prescriptive legal study highlights the urgency of revising the Notary Law and Permenkumham No. 19 of 2019 to guarantee professionalism and legal protection for service users. The results of the study indicate the urgency of revising the provisions in the Notary Law and the Regulation of the Minister of Law and Human Rights Number 19 of 2019, especially those regulating the requirements and position of Substitute Notaries, in order to guarantee professionalism and legal protection for the community using notary services.